Commodifying Java Coffee: An Analysis using Spivak’s Planetarity toward Dee’s Filosofi Kopi - Apristia, Lelu Dina (POETIKA, 2023)
This research aims to analyze how and why Java coffee depicted by Kopi Tiwus in Dee’s Filosofi Kopi is commodified after Dutch colonialism which is inseparable from Eurocentrism ended in 1945 when Indonesia gained its independence. After applying qualitative research method with a post-colonial approach which involves collecting data in the form of words and analyzing the data by using Spivak’s planetarity as a post-colonial theory, it is found that the coffee is commodified through interaction between global agents depicted by Ben and Jody as owners of a coffee shop in Jakarta, namely Filosofi Kopi, and planetary subjects depicted by a middle-aged man with a strong Javanese accent who makes Ben and Jody know the coffee and by Pak Seno who sells it in a rickety hut in a rural area which is not far from Klaten, Central Java. Through the interaction, knowledge of features of Java coffee which is produced in smallholder coffee plantations on Java Island, Indonesia suggesting the country to enlarge its coffee plantations and to provide information and assistance of coffee cultivation technology to raise competitiveness of its coffee in the world market can be exchanged. The features are well-grown in a fertile land, the highest quality type of coffee, and brewed in a simple way which lead Java coffee to become a commodity to generate capital which can be globalized as well as European coffee depicted by Ben’s Perfecto as Ben’s creation together with a variety of popular espresso drinks. Made with espresso method and machine found and developed by Europeans along with other coffee brewing equipment and tools being homogenized in numerous cafes around the world, including in Indonesia, European coffee can be juxtaposed with Java coffee which does not require use of the machine and thus regarded as a different one. Novelty of the research is commodifying Java coffee without alienation of labor as Spivak states that planetarity keeps homogenization and differentiation in alterity which makes planetarity “in excess” of globalization of capital.